2019
DOI: 10.4028/www.scientific.net/kem.803.351
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Solvent Polarity on Phase Transformation of Citrogypsum via Hydrothermal Process

Abstract: Calcium sulfate dihydrate (CaSO4•2H2O, CSD), gypsum is a by-product in the production of citric acid (citryogypsum). This by-product could neither be exploited nor distributed as a reactant because of its physical properties including those that are not equivalent to natural gypsum. Moreover, the mentioned citrogypsum has been continually increasing environmental problems. Therefore, this research aims at how to recycle gypsum that is synthesized by hydrothermal method at 95oC for 7 hrs under the atmospheric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…In the other hand, when 4M and 5M sodium chloride solutions are employed in the reaction process, the transformation of citrogypsum to α-HH are achieved which confirmed by the absent of characteristic peaks of DH, and the exothermic peak are presented at 290 to 300ᵒC. Hence, it is concluded that the citrogypsum is successfully transformed of to α-HH [2][3]. The SEM micrographs in Fig.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…In the other hand, when 4M and 5M sodium chloride solutions are employed in the reaction process, the transformation of citrogypsum to α-HH are achieved which confirmed by the absent of characteristic peaks of DH, and the exothermic peak are presented at 290 to 300ᵒC. Hence, it is concluded that the citrogypsum is successfully transformed of to α-HH [2][3]. The SEM micrographs in Fig.…”
Section: Resultsmentioning
confidence: 74%
“…In addition, α-HH is usually used because of better workability and higher strength. The preparation of single crystal α-HH from citrogypsum raw material [1][2][3], hydrothermal, is a simple and effective at a high temperature and pressure. The previously work of the flue gas desulfurization gypsum (FGD gypsum) transformation to α-HH in saline solution are successfully done, however the citrogypsum from citric acid production could not be converted to α-HH under this condition.…”
Section: Introductionmentioning
confidence: 99%
“…Цитрогипс, являющийся отходом биохимического производства лимонной кислоты [16,17] (Белгород, Россия), служил исходным материалом для изготовления датчиков влажности воздуха. Физические и химические свойства цитрогипса описаны в [18].…”
Section: материалы и методыunclassified
“…However, CG so synthesized is not industrially acceptable because he physical and chemical properties are inferior to natural gypsum. It cannot be used to form white products [3].…”
Section: Introductionmentioning
confidence: 99%